Tracheal Diverticulum in SARS-CoV-2 Patients on Non-Invasive Ventilation A not so “Spontaneous” Cause of Pneumomediastinum? An imaging Pictorial Presentation of Two Cases with Review of Literature - Joseph, Veena Mariam; Lynser, Donboklang; Tiewsoh, Iadarilang; Dutta, Kaustuv; Phukan, Pranjal; Daniala, Chhunthang (Acta medica Lituanica, 2021)
Spontaneous pneumomediastinum is a rare but potentially life-threatening condition, the incidence of which has showed an increase in patients with SARS-CoV-2 pneumonia, especially when they are on positive pressure ventilation. None of the reported cases of covid related pneumomediastinum had an associated tracheal diverticulum. Also, to the best of our knowledge, tracheal diverticulum has not been reported in patients on NIV. We report 2 cases of COVID-19 pneumonia on NIV with pneumomediastinum, which also had associated tracheal diverticulum, one of which developed after NIV. Though the establishment of causality needs further research, early detection of a tracheal diverticulum, which might be a harbinger of pneumomediastinum, can be a timely alarm to prompt titration of the pressure settings and judicious use of NIV. The role of inverted grey scale CT images in mediastinal window is a simple, yet hardly utilised radiological tool to increase detection of ‘mediastinal air’, let it be free air or air within a diverticulum. Through this case report, we would like to highlight the role of conventional and inverted CT imaging of pneumomediastinum and tracheal diverticulum in general and in SARS-CoV-2 pneumonia in particular, and to call for more objective research to throw light on the plausible relationship between pneumomediastinum and tracheal diverticulum.